Investigation of laser cooling and trapping of atomic silicon: towards the development of a deterministic single ion source - Ronald, Samuel R., author; Lee, Siu Au, advisor; Fairbank, William M., Jr., advisor; Rocca, Jorge J., committee member; Marconi, Mario C., committee member (Colorado State University. Libraries, 2023)
The laser cooling and magneto-optical trapping of silicon atoms were investigated experimentally. These are the first steps towards the development of a deterministic single ion source suitable for single ion implantation of a Kane quantum computer. We identified the 3s23p2 3P2 → 3s3p3 3Do3 transition at 221.74nm as a cycling transition suitable for laser cooling. We also identified the 3s23p2 1D2 → 3s3p3 3Do3 at 256.26nm as a repump transition coupling a lower metastable state with the upper cooling state. Two deep ultraviolet (DUV) laser systems were implemented to provide the cooling and repump laser light. Both systems utilized two stage second harmonic generation to quadruple the frequency of a fundamental laser to produce the DUV light. The cooling laser system utilized frequency quadrupling of a tunable cw Ti:Sapphire ring laser to produce up to 90mW at 221.74nm. The repump laser system utilized frequency quadrupling of an external cavity diode laser to produce up to 35mW at 256.26nm. A silicon atomic beam source operating at 1400°C was developed that produced a beam of free silicon atoms for laser studies. The atomic beam characteristics were analyzed, and the velocity distribution was manipulated via laser cooling. Careful spectroscopic studies were performed on the cooling and repump transitions. Frequency references for the DUV lasers were investigated in Te2 and I2 with Doppler free saturated absorption spectroscopy, using the first doubling stage output of the cooling and repump laser, respectively. Specific hyperfine components of the molecular transitions in Te2 and I2, suitable for frequency references, were identified and measured. Locking of the cooling laser on the Te2 reference was demonstrated. A magneto-optic trap (MOT) was implemented in the silicon atomic beam. A CCD optical system to image the fluorescence from atoms in the MOT was developed and achieved single atom ii detection capability. MOT trapping of silicon atoms was attempted. The low flux of atoms in the MOT velocity capture range precluded any observation of trapped atoms. A Zeeman slower, based on a novel design utilizing a variable pitch helical solenoid, was designed, simulated, and constructed to improve the flux of slow atoms. No magneto-optic trap was observed due to insufficient laser power for simultaneous Zeeman slowing and magneto-optic trapping. Investigations were performed for one dimensional laser cooling, via a Zeeman slower, along the atomic beam motion direction. Atomic beam velocity distribution profiles were observed to be modified when the Zeeman slower was on. The parameter space of Zeeman slower currents, laser power and detuning, was explored. A simulation of the atom motion over the 1m long flight path under the influence of the Zeeman slower was carried out and found to agree with the observed results.